CHILDREN SOMATOTYPE STUDY OF DIFFERENT ETHNIC GROUPS FROM PLOVDIV REGION, BULGARIA - Atanas Baltadjiev; Elena Merdzhanova; Nikolay Boyadjiev; Penka Angelova; Ralitza Raycheva; Valentina Lalova; Gergana Petrova (Journal of IMAB, 2024)
The purpose of the present study was to determine and compare the children's somatotypes of three ethnic groups living in the Plovdiv region, Bulgaria. Material and Methods: A cohort of 194 children were enrolled in the study. They were divided into four groups by sex and age. Each group were divided by ethnicity into three subgroups: Bulgarian, Turkish and Roma origins. The regression equations introduced by Heath and Carter were used to determine the somatotype components. Results: The somatotype of Bulgarian and Roma boys aged 11-12 years was defined as mesomorph-endomorph, while the somatotype of Turkish boys was determined as central. The somatotype of boys aged 13-14 years was defined as follows: Bulgarian boys- balanced endomorph, Turkish boys- endomorph-ectomorph and Roma boys with central somatotype. The mean somatotype of Bulgarian girls aged 11-12 years was defined as ectomorphic an endomorph, while the somatotype of both Turkish and Roma girls was defined a mesomorphic endomorph. Similar results were found analyzing the mean somatotype of girls aged 13-14 years. Conclusion: The period of puberty has a very important impact on the development of the human body. The mean somatotype of Bulgarian boys aged 11-12 years has changed from mesomorph-endomorph to balanced endomorph. The mean somatotype of Turkish boys aged 11-12 has changed from central to endomorph-ectomorph. The mean somatotype of Roma boys aged 11-12 has changed from mesomorph-endomorph to central. The mean somatotype of Bulgarian girls was ectomorphic endomorphic; for Turkish and Roma girls it was mesomorphic endomorphic for both age group.